Urochloa ruziziensis cover crop increases the cycling of soil inositol phosphates - Almeida, Danilo S.; Menezes-Blackburn, Daniel; Turner, Benjamin L.; Wearing, Catherine; Haygarth, Philip M.; Rosolem, Ciro A. (Biology and fertility of soils, 2018)
Ruzigrass ( Urochloa ruziziensis ) is a cover crop that is commonly used in Brazil and exudes high concentrations of organic acids from its roots, and is therefore expected to mobilize soil organic P such as inositol phosphates. However, it is not known if this can occur only under P deficient conditions. Specifically, we aimed to test the hypothesis that the degradation of inositol phosphates is increased by growing ruzigrass at two different P levels. To investigate this, we studied soil organic P in a 9-year-old field experiment, with treatments consisting of ruzigrass or fallow during the soybean ( Glycine max ) off-season, with or without P addition. Organic P was extracted in NaOH-EDTA, followed by colorimetric quantification of organic P hydrolysable by phytase, and myo -inositol hexakisphosphate by hypobromite oxidation and HPLC separation. Ruzigrass dry matter yield increased by about 80% with P application. Ruzigrass reduced the concentration of phytase labile P and myo -inositol hexakisphosphate, but only in soil receiving P. A corresponding increase in unidentified inositol phosphates, presumably representing lower-order esters, was also observed after ruzigrass in soil with P application. We deduce that the degradation of inositol phosphates under ruzigrass with P application is due to greater ruzigrass productivity in the more fertile treatment, increasing the release of root exudates that solubilize inositol phosphates and promote their decomposition by phytase. We conclude that ruzigrass cover cropping can promote the cycling of recalcitrant soil organic P, but only when fertility is raised to a sufficient level to ensure a productive crop.